Investigating the effect of the aroma inhalation of orange and lavender essential oils in comparison with placebo on the level of anxiety in clients in a dental clinic in Shiraz: a double-blind controlled randomized clinical trial - Samaneh Hasanshahi; Mohammad Mahdi Parvizi; Masoud Bahreini; Shahnaz Pouladi; Kamran Mirzaei (Institue of Medicinal Plants, ACECR, 2020)
Background: Attending a dentist and placing on the unit can cause anxiety. Objective: The aim of this study was to compare the effect of the aroma inhalation of orange and lavender essential oils in comparison with placebo on the level of anxiety in clients in a dental clinic in Shiraz. Methods: This randomized double-blind clinical trial was performed on 120 patients referred to a Dental Clinic. The patients were divided into three groups of anxiety treatments with scent of lavender, orange and sesame (as control). The Spielberger questionnaire was used to measure the anxiety of the patients before and after the study. Data were analyzed by SPSS version 22. The level of significance was considered as 5%. Results: Overall, there is no difference in the state scores of anxiety before and after the interventions. In the sesame group (t-test (-0.068) and the significant level (0.501), in the orange group (t (0.465) and significant level (0.645), in the lavender group (t (0.321) and significant level (0.750). However, a statistically significant difference was observed between the levels of state and trait anxiety after the interventions in all three groups. Conclusion: Although, based on the present study, the use of orange and lavender extracts had partially reduced the levels of state and trait of anxiety in dental clients, more clinical studies are recommended.